2019
DOI: 10.1016/j.automatica.2019.108597
|View full text |Cite
|
Sign up to set email alerts
|

Controllability of Kronecker product networks

Abstract: A necessary and sufficient condition is derived for the controllability of Kronecker product networks, where the factor networks are general directed graphs. The condition explicitly illustrates how the controllability of the factor networks affects the controllability of the composite network. For the special case where at least one factor network is diagonalizable, an easilyverifiable condition is explicitly expressed. Furthermore, the controllability of higher-dimensional multi-agent systems is revisited, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Graph node partitions were subsequently employed to characterize the upper bounds on the dimension of the controllable subspace of multi-agent networks [5], [6], [7]; analogous lower bounds have also been derived using distance partitions [5], [8]. Due to the difficulty in analyzing controllability of general networks, controllability for special classes of networks has been an active area of research [9], [10], [11], [12], [13], [14]. Recently, controllability of multi-agent system on signed networks (where cooperative and competitive interactions coexist) has also received attention.…”
Section: Introductionmentioning
confidence: 99%
“…Graph node partitions were subsequently employed to characterize the upper bounds on the dimension of the controllable subspace of multi-agent networks [5], [6], [7]; analogous lower bounds have also been derived using distance partitions [5], [8]. Due to the difficulty in analyzing controllability of general networks, controllability for special classes of networks has been an active area of research [9], [10], [11], [12], [13], [14]. Recently, controllability of multi-agent system on signed networks (where cooperative and competitive interactions coexist) has also received attention.…”
Section: Introductionmentioning
confidence: 99%
“…Extensions of KPGM also include, for instance, a tied KPGM which accounts for variance in network populations (Moreno et al, 2010), a block-KPGM capturing a fractal structure observed in many real world networks (Moreno et al, 2013), an enhanced version of the KPGM which uses random noise for smoothing (Seshadhri et al, 2013), and a mixture-model based KPGM (Mahapatra & Chandola, 2015). Recently, Hao et al (2019) study the controllability of KPGM, while Ma et al (2019) investigate the existence of restricted edge connectivity, that is, the minimum number of edges whose deletion disconnects the graph, of KPGM.…”
Section: Kronecker Product Graph Modelmentioning
confidence: 99%
“…The controllability of heterogeneous networked systems was investigated in [27]. The controllability conditions for networked systems with more complicated structure, such as deep-coupling networks [28] and Kronecker product networks [29] were also derived.…”
Section: Introductionmentioning
confidence: 99%